Information System for Calculating Daily Sugar Limits in Consuming Web-Based Packaged Drinks Using the Prototype Method - Wirasa, Galuh Panca; Azhar, Nur Chalik (Universitas Trilogi, 2025)
Excess sugar consumption is a global concern as it plays an active role in increasing the risk of non-communicable diseases (NCDs) such as obesity, type 2 diabetes and heart disease. In Indonesia, intense consumption of sugary packaged drinks is influenced by lifestyle changes and low public awareness of its impact. This study develops a web-based system to help users determine the safe limit of consumption of packaged sugary drinks, based on daily calorie needs calculated using the Mifflin-St Jeor formula. the application was designed using the prototype method to ensure interactive and user-oriented development. Assessment conducted through the System Usability Scale (SUS) method indicated that the prototype achieved an average score of 76.6, placing it in the 'Good' classification with a Grade B rating. This finding proves that the system has a good level of usability and is acceptable to users. This system has the potential to become an educational media that supports increasing public awareness of the dangers of excessive sugar consumption, through providing information that is easily accessible and easy to understand, and is expected to contribute to efforts to prevent non-communicable diseases (NCDs) in Indonesia.